2020
DOI: 10.3847/1538-4357/aba94b
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Late-stage Reconnection in the 2017 September 10 Solar Flare

Abstract: In this multi-instrument paper, we search for evidence of sustained magnetic reconnection far beyond the impulsive phase of the X8.2-class solar flare on 2017 September 10. Using Hinode/EIS, CoMP, SDO/AIA, K-Cor, Hinode/ XRT, RHESSI, and IRIS, we study the late-stage evolution of the flare dynamics and topology, comparing signatures of reconnection with those expected from the standard solar flare model. Examining previously unpublished EIS data, we present the evolution of nonthermal velocity and temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…The delayed component of the GLE also decayed but with a longer decay time. In the late phase of the flare, the main flare arcade continued to rise (Figure 5 of French et al 2020) and a number of fast evolutions were observed in the southern loop system (Figure 2(b)), while MW and HXR emissions declined. A prominent association is the low-frequency type II radio burst observed by STEREO A/WAVES at 16:50 UT-19:40 UT on 2017 September 10 between 0.3 MHz and 1.6 MHz (Figure 9 of KPL20).…”
Section: High-energy Event Morphology and Associationsmentioning
confidence: 99%
“…The delayed component of the GLE also decayed but with a longer decay time. In the late phase of the flare, the main flare arcade continued to rise (Figure 5 of French et al 2020) and a number of fast evolutions were observed in the southern loop system (Figure 2(b)), while MW and HXR emissions declined. A prominent association is the low-frequency type II radio burst observed by STEREO A/WAVES at 16:50 UT-19:40 UT on 2017 September 10 between 0.3 MHz and 1.6 MHz (Figure 9 of KPL20).…”
Section: High-energy Event Morphology and Associationsmentioning
confidence: 99%
“…The subsequent evolution of the instability and turbulent energy spectrum is consistent with previous work by Dong et al (2018) and Tenerani & Velli (2020) that supports the presence of the combined effects of dynamic alignment of the magnetic islands (or plasmoids), intermittency, and recursive reconnection. We note that recent work by French et al (2019French et al ( , 2020 provides an important new tool for quantifying the internal substructure of current sheets that can be used to further probe alignment and intermittency.…”
Section: Discussionmentioning
confidence: 97%
“…The most successful spectroscopic plasma sheet observation set to date originated from the famous 2017 September 10 X-class flare (Warren et al 2018). This event was observed by multiple instruments across the entire electromagnetic spectrum, facilitating insight into the nature of magnetic reconnection in the event, and providing initial evidence for the presence of turbulent or tearing mode reconnection (Cheng et al 2018;French et al 2019), persisting for the flare's entire duration (French et al 2020). Although observations of this 2017 September 10 event provided many new insights into the behavior of current sheet dynamics, the uniqueness of such a data set requires alternative methods to be employed in order to make further progress in understanding these processes.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent evolution of the instability and turbulent energy spectrum is consistent with previous work by Dong et al (2018) and Tenerani & Velli (2020) that supports the presence of the combined effects of dynamic alignment of the magnetic islands (or plasmoids), intermittency and recursive reconnection. We note that recent work by French et al (2019French et al ( , 2020 provides an important new tool for quantifying the internal sub-structure of current sheets that can be used to further probe alignment and intermittency.…”
Section: Discussionmentioning
confidence: 97%
“…The most successful spectroscopic plasma sheet observation set to date originated from the famous September 10th 2017 X-class flare (Warren et al 2018). This event was observed by multiple instruments across the entire electromagnetic spectrum, facilitating insight into the nature of magnetic reconnection in the event, and providing initial evidence for the presence of turbulent or tearing-mode reconnection (Cheng et al 2018;French et al 2019), persisting for the flare's entire duration (French et al 2020). Although observations of this September 10th 2017 event provided many new insights into the behaviour of current sheet dynamics, the uniqueness of such a dataset requires alternative methods to be employed in order to make further progress in understanding these processes.…”
Section: Introductionmentioning
confidence: 99%